Entrepreneurial Ecosystem: A Systematic Literature Review - Rahul Krushnaji Wadichar; Prashant Manusmare, Mukul Abasaheb Burghate
Entrepreneurial ecosystems (EEs) is a relatively new concept that has piqued the curiosity of legislators, researchers and professionals. Despite the fact that research on EES is growing, their inputs are still dispersed. No studies have attempted to combine the available research on EES because the literature is fragmented. As a result, the goal of this study is to perform a systematic literature review on EES. This assessment of the literature looks at research included in the Scopus and web of science indexed journals publication like Emerald, Science Direct (Elsevier), JSTOR, SAGE and Google Scholar. The purpose of this research is to uncover research gaps and flaws in the field of entrepreneurial ecosystem (EE). The results reveal that the emergence of EEs is poorly understood, with conceptual research dominating in recent years. By recognizing research gaps in the current literature, we provide a road map for future entrepreneurial environment research. Cooperation, knowledge exchange and innovation at the higher levels are more likely to produce favourable entrepreneurship environments. It identifies present gaps in theories and empirical studies as well as potential research directions in EEs.